Classification of inferior articular process injury after percutaneous endoscopic interlaminar lumbar discectomy based on CT three-dimensional reconstruction and its clinical significance - Haigang Hu; Chao Wu; Tao Li; Hong Li (BMC Musculoskeletal Disorders)
Abstract Objective To propose a new classification method based on CT three-dimensional reconstruction for inferior articular process injury following percutaneous endoscopic interlaminar lumbar discectomy (PEID), and to analyze the impact of > 50% inferior articular process(IAP) defect on clinical outcomes. Methods A retrospective analysis was conducted on 100 PEID patients. IAP injuries were classified into four types based on CT three-dimensional reconstruction, and the inter- and intra-observer reliability was assessed using the Kappa consistency test. Patients were divided into two groups based on IAP defect size: Group A (defect ≤ 50%) and Group B (defect > 50%). VAS, ODI, clinical outcomes, and lumbar instability were compared between the two groups, and IAP changes were observed. Results The classification showed good inter- and intra-observer consistency. There were no significant differences in VAS, ODI, clinical outcomes, or lumbar instability between the two groups (P > 0.05). Both groups showed varying degrees of IAP regeneration and remodeling. Conclusion The classification of IAP injuries based on CT three-dimensional reconstruction demonstrates good inter- and intra-observer consistency. In the short term, patients with > 50% IAP defects (Types III and IV) show no difference in lumbar stability or clinical outcomes compared to those with ≤ 50% defects (Types I and II).However, for patients with complete IAP loss (Type IV), the potential long-term risk of lumbar instability and related clinical complications remains a concern.